Socio-Economic Upliftment of Tribal Women through FPO in Bastar District of Chhattisgarh - Rathour, Virendra; Tiwari, P. K.; Pandey, P. K.; Singh, K. P.; Singh, D. P. (Indian Journal of Extension Education, 2022)
The study was carried out in Bastar district of Chhattisgarh state during 2021-22. The findings depicted that on the basis of their membership period in Bhumigadi Mahila Krushak Farmer Producer Organization (BMKFPO); the 37.28 per cent increase (Rs. 11653/-) was recorded for the member of BMKFPO since last four years whereas 36.81 per cent (Rs. 11456/-), 32.97 per cent (Rs. 10203/-) and 31.62 per cent (Rs. 9420/-) increase in income were recorded for the member of FPO since last three years, two years and one year respectively. The significance level of differences in income of respondents before and after joining the BMKFPO, Bastanar; P value were recorded as 0 (p=0, p=
Keywords: Women empowerment; Socio economic status; Income generating activities; BMKFPO; Bastanar